Bright and Dark Soliton Solutions of the (2+1)-Dimensional Evolution Equations - Bekir, Ahmet; Cevikel, Adem C.; Guner, Ozkan; San, Sait (VILNIUS GEDIMINAS TECH UNIV, 2014)
In this paper, we obtained the 1-soliton solutions of the (2+1)-dimensional Boussinesq equation and the Camassa-Holm-KP equation. By using a solitary wave ansatz in the form of sech(p) function, we obtain exact bright soliton solutions and another wave ansatz in the form of tanh(p) function we obtain exact dark soliton solutions for these equations. The physical parameters in the soliton solutions are obtained nonlinear equations with constant coefficients.
Keywords: exact solutions; bright and dark solitons; Boussinesq equation; Camassa-Holm-KP equation; TRAVELING-WAVE SOLUTIONS; TANH-FUNCTION METHOD; SINE-COSINE METHOD; NONLINEAR EVOLUTION; EXPANSION METHOD; Mathematics